CHARACTERISTIC SYMPTOMS OF CHILDREN WITH LEARNING DISABILITY IN RELATION TO COGNITIVE FUNCTION - Madhurima Rani (International Journal of Multidisciplinary Research and Studies, 2021)
According to Duncan et al. (2007), mathematics aptitude before to entering school is one of the greatest indicators of educational performance. This is because arithmetic is an essential skill in a contemporary society. The expenses associated with inadequate numeracy are difficult to determine, although they are significant. had been projected to amount to 763 million pounds annually inside the United Kingdom alone (Every Child a Chance Trust, 2009). Low numeracy might be associated to special seducational requirements, school failure, antisocial conduct etc.